2012
DOI: 10.1007/s00198-011-1882-9
|View full text |Cite
|
Sign up to set email alerts
|

Short-term teriparatide therapy as an adjunctive modality for bisphosphonate-related osteonecrosis of the jaws

Abstract: In terms of the multifactorial etiology of BRONJ, bone formation suppression was noticed in the patients. Based upon this finding, the short-term use of teriparatide might be beneficial to the resolution of BRONJ lesions by improving suppressed bone remodeling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 20 publications
1
36
0
1
Order By: Relevance
“…It might also improve healing of osteonecrosis of the jaw induced by inhibitors of bone resorption [163].…”
Section: Peptides From the Parathyroid Hormone Familymentioning
confidence: 99%
“…It might also improve healing of osteonecrosis of the jaw induced by inhibitors of bone resorption [163].…”
Section: Peptides From the Parathyroid Hormone Familymentioning
confidence: 99%
“…5 Although development of osteosarcoma was not reported in humans, there is no longterm information, thus TP treatment for more than 2 years is not recommended. 37 In the previously reported case reports, TP was injected for 1-6 months in BRONJ treatment and is considered to be a short-term treatment. 37 TP, which is indicated in osteoporosis prevention and treatment, is also indicated in osteoporotic BRONJ patients.…”
Section: Discussionmentioning
confidence: 99%
“…37 In the previously reported case reports, TP was injected for 1-6 months in BRONJ treatment and is considered to be a short-term treatment. 37 TP, which is indicated in osteoporosis prevention and treatment, is also indicated in osteoporotic BRONJ patients. Although TP is contraindicated in patients who have malignant bone diseases and developed BRONJ, 28 studies on the suitability of short-term TP therapy in these patients are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Bisphosphonates exert their anti-resorptive activity by suppression of osteoclasts. A few clinical cases have reported the successful off-label use of teriparatide for treating ONJ (Harper and Fung, 2007;Lau and Adachi, 2009;Cheung and Seeman, 2010;Narongroeknawin et al , 2010;Tsai et al ., 2010;Lee et al , 2011;Kwon et al , 2012;Narvaez et al , 2012). Teriparatide increases bone remodeling and has been reported to reduce microdamage accumulation in the bone, a possible etiology of ONJ.…”
Section: Dental Implant and Implant-related Bone Augmentation Proceduresmentioning
confidence: 99%
“…Animal models with/without induced osteoporosis and gene ablation models support the impact of PTH on bone development and remodeling in the craniofacial region, thus providing a sound rationale for the use of PTH for applications in oral and maxillofacial bone regeneration (Kawane et al, 2002;Rowshan et al, 2010;Valderrama et al, 2010). Preliminary clinical studies have shown promising results with teriparatide for periodontal regeneration and the treatment of osteonecrosis of the jaw related to the use of bone antiresorptive drugs (Tsai et al, 2010;Lee et al, 2011;Kwon et al, 2012). This review will update research on the impact of PTH in the craniofacial skeletal, regeneration applications, and future prospects for clinical benefits of PTH therapy.…”
Section: Introduction Tmentioning
confidence: 99%